Calculation model of concrete-filled steel tube arch bridges based on the “arch effect” - Wang, Shaorui; Li, Yingbin; Liu, Zengwu; Cheng, Tianlei (Frontiers in Materials, 2023)
Given the present specification based on the equivalent Liang Zhufa “rod model” instead of the “arch model” have limitations when performing calculations related to concrete-filled steel tubular arch bridge, the arch and the load-bearing mechanism of eccentric compression column are analyzed based on the real bearing mechanism of the arch. The single pipe concrete-filled steel tube arch model test was conducted to analyse arch deformation state and failure mode. The measured geometric nonlinear bending moment of the arch is compared with the bending moment calculated by the “rod mode” eccentricity increment coefficient. The results showed that the transfer of the arch internal force is from the axial force to the arch axis , causing the vertical reaction force and horizontal thrust, which combined with the deformation directly generated by the external load leads to the additional bending moment. However, the eccentric compression column only produces the vertical force at the bottom, and combines with the lateral deformation indirectly generated by the eccentric distance leads to the additional bending moment. In addition, the deformation stage of the arch is basically the same as that of eccentric compression column. The final failure mode of arch is 4 hinged arch, and the final failure mode of eccentric compression column is single hinge damage. The preliminary geometric nonlinear bending moment value obtained by two modes accord well. But late showed the control section measured values is less than calculated value, the other section is greater than the calculated value. Therefore, according to the analysis and test results, the following conclusions can be drawn: the main factors for the difference in bearing mechanism between the two modes are different force structures, force transmission routes, and sources of deformation. Due to the difference in the bearing mechanism of the two modes, the final failure mode is different, and the deformation ability of the arch is weakened by using “rod mode” instead of “arch mode”. The geometric nonlinear bending moment of the control section calculated by the coefficient of eccentricity increase is conservative, but the influence of the geometric nonlinearity of other sections is not considered enough.